2021
DOI: 10.1001/jamadermatol.2020.5732
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stigma Toward Individuals With Alopecia

Abstract: IMPORTANCEPerceived stigma among patients with alopecia is associated with impaired quality of life; however, the magnitude of laypersons' stigma toward individuals with alopecia is unknown.OBJECTIVE To determine the prevalence and magnitude of laypersons' stigma toward individuals with varying degrees of alopecia and whether stigma increases with increased severity of alopecia. DESIGN, SETTING, AND PARTICIPANTSThis was a cross-sectional study using an internet survey administered to a convenience sample of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…This and other studies have demonstrated that hair loss is psychosocially burdensome to patients and time‐consuming and difficult to hide 9,16–22 . Patients have demonstrated proficiency in assessing their own hair loss and informed that near‐complete scalp hair regrowth (≤ 20% missing hair/SALT score ≤ 20) would restore a sense of normality 28,33,36 .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…This and other studies have demonstrated that hair loss is psychosocially burdensome to patients and time‐consuming and difficult to hide 9,16–22 . Patients have demonstrated proficiency in assessing their own hair loss and informed that near‐complete scalp hair regrowth (≤ 20% missing hair/SALT score ≤ 20) would restore a sense of normality 28,33,36 .…”
Section: Discussionmentioning
confidence: 90%
“…This and other studies have demonstrated that hair loss is psychosocially burdensome to patients and time-consuming and difficult to hide. 9,[16][17][18][19][20][21][22] Patients have demonstrated proficiency in assessing their own hair loss and informed that near-complete scalp hair regrowth (≤ 20% missing hair/SALT score ≤ 20) would restore a sense of normality. 28,33,36 Therefore, it is not only feasible but critically important to assess the clinical signs of AA, including scalp hair loss, from the patient perspective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the Editor: Patients with alopecia areata (AA) are commonly assumed to be sick or have cancer, especially when they have severe loss of scalp and eyebrow or eyelash hair. 1 Many patients report being told by strangers to ''keep up the fight'' or that they will be included in their prayers. Families recount experiences in which they have been given special treatment, such as having a meal paid for or an admission fee waived at a museum or amusement park.…”
mentioning
confidence: 99%